2019
DOI: 10.1039/c9ra00505f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric enhancement of the detection of H2O2using different organic substrates and a peroxidase-mimicking polyoxometalate

Abstract: A fluorometric enhancement method based on a polyoxotungstate intrinsic peroxidase for the detection of hydrogen peroxide under basic conditions is developed for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The theoretical LOD was 1.0 mM, estimated using the 3sblank criterion. This LOD is higher than the LOD of silver NPs modified cellulose nanowhiskers [ 79 ], polyoxometalate [ 80 ], Ce 2 (WO 4 ) 3 , papain [ 81 ], Ag-nanoparticle-decorated silica microspheres [ 82 ] and magnetic mesoporous silica nanoparticles [ 83 ]. These results suggest that this material can be used to detect H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical LOD was 1.0 mM, estimated using the 3sblank criterion. This LOD is higher than the LOD of silver NPs modified cellulose nanowhiskers [ 79 ], polyoxometalate [ 80 ], Ce 2 (WO 4 ) 3 , papain [ 81 ], Ag-nanoparticle-decorated silica microspheres [ 82 ] and magnetic mesoporous silica nanoparticles [ 83 ]. These results suggest that this material can be used to detect H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Tian et al ( Tian et al, 2019 ) reported the synergetic combination of organic species such as benzoic acid (BA), thiamine (TH), and 3-(4-hydroxyphenyl)propionic acid (HPPA), with the Keggin-type polyoxotungstate intrinsic peroxidase Na 10 [ α -SiW 9 O 34 ] decomposing H 2 O 2 into ▪OH radicals, which converted weakly fluorescent substrates to strongly fluorescent substrates, under basic pH conditions. Recently, S-/N-containing ligands, such as 2,2′-dimethyl-4,4′-bithiazole ( Ying et al, 2019 ; Wang et al, 2020b ) and 2,5-bis(4-pyridyl)thiazolo [5,4- d ] thiazole ( Mou et al, 2020 ), and N-containing ligands, such as 2,2′-bipyridyl (bpy) and 4-(3-imidazol-1-yl-ethyl)-4H-[1,3,4]triazole (MET) ( Zhang et al, 2021a ) were used to modify a series of different archetype POM compounds, in order to build fluorescence sensors for Hg 2+ .…”
Section: Polyoxometalates Functionalized Sensorsmentioning
confidence: 99%
“…The absorbance values were increased with an increasing amount of NFs and length of time. According to a method described previously [26][27][28][29][30], the mechanism of peroxidase-like catalytic activities of Hb-Cu 3 (PO 4 ) 2 NFs can be further investigated using steady-state kinetic assays at pH 10. As shown in Figure S6, a typical Michaelis-Menten curve was obtained for Hb-Cu 3 (PO 4 ) 2 NFs in the presence of H 2 O 2 and OPD, respectively.…”
Section: Enzyme-like Activities and Kinetic Parameters Of Hb-cu 3 (Po 4 ) 2 Nfsmentioning
confidence: 99%